Acute Bladder Necrosis after Pelvic Arterial Embolization for Pelvic Trauma: Lessons Learned from Two Cases of Immediate Postembolization Bladder Necrosis. (5th September 2016) - Washington, Samuel; Osterberg, E. Charles; Elliott, Sean P.; Hittelman, Adam B.; Breyer, Benjamin N.
Abstract : We report two cases of acute bladder injury with bladder neck necrosis identified during the initial operative evaluation and within the early postprocedural period in patients with significant pelvic trauma requiring pelvic vascular embolization. To our knowledge, this is the first report of bladder neck necrosis found during the initial intraoperative surgical evaluation or early postoperative setting.